2022
DOI: 10.1038/s41598-022-17725-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunological profiles associated with distinct parasitemic states in volunteers undergoing malaria challenge in Gabon

Abstract: Controlled human malaria infection (CHMI) using cryopreserved non-attenuated Plasmodium falciparum sporozoites (PfSPZ) offers a unique opportunity to investigate naturally acquired immunity (NAI). By analyzing blood samples from 5 malaria-naïve European and 20 African adults with lifelong exposure to malaria, before, 5, and 11 days after direct venous inoculation (DVI) with SanariaR PfSPZ Challenge, we assessed the immunological patterns associated with control of microscopic and submicroscopic parasitemia. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…A recent study found out that PfSPZ vaccination-induced parasite control in malaria-exposed individuals was associated with IFN-γ-and TNF-co-producing γδ T cells together with IFN-γ-producing CD4 + T cells. 22 Although all sporozoite vaccination studies support the protective roles of γδ T cells, it is not clear whether their function in protection is purely as an effector or assist in inducing DCs or CD8 + T cells. Furthermore, better understanding of the biology and function of liver γδ T cells will be a valuable tool for developing PfSPZ-based vaccines for the induction of sterile immunity.…”
Section: γδ T Cells In Response To Plasmodium Sporozoite Vaccination:...mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found out that PfSPZ vaccination-induced parasite control in malaria-exposed individuals was associated with IFN-γ-and TNF-co-producing γδ T cells together with IFN-γ-producing CD4 + T cells. 22 Although all sporozoite vaccination studies support the protective roles of γδ T cells, it is not clear whether their function in protection is purely as an effector or assist in inducing DCs or CD8 + T cells. Furthermore, better understanding of the biology and function of liver γδ T cells will be a valuable tool for developing PfSPZ-based vaccines for the induction of sterile immunity.…”
Section: γδ T Cells In Response To Plasmodium Sporozoite Vaccination:...mentioning
confidence: 99%
“…In malaria‐naïve individuals activated effector γδ T cells were maintained for 14 months without further exposure, 21 suggesting the formation of long‐lasting memory γδ T cells. A recent study found out that PfSPZ vaccination–induced parasite control in malaria‐exposed individuals was associated with IFN‐γ– and TNF‐co‐producing γδ T cells together with IFN‐γ–producing CD4 + T cells 22 . Although all sporozoite vaccination studies support the protective roles of γδ T cells, it is not clear whether their function in protection is purely as an effector or assist in inducing DCs or CD8 + T cells.…”
Section: γδ T Cells In Response To Plasmodium Sporozoite Vaccination:...mentioning
confidence: 99%